2021
DOI: 10.1371/journal.pone.0260690
|View full text |Cite
|
Sign up to set email alerts
|

Quality-adjusted life year comparison at medium term follow-up of endovascular versus open surgical repair for abdominal aortic aneurysm in young patients

Abstract: Objectives This study aimed to compare the quality of life and cost effectiveness between endovascular aneurysm repair (EVAR) and open surgical repair (OSR) in young patients with abdominal aortic aneurysm (AAA). Design This was a single-center, observational, and retrospective study. Materials and methods A retrospective analysis was conducted of patients with AAA, who were <70 years old and underwent EVAR or OSR between January 2012 and October 2016. Only patients with aortic morphology that was suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The initial procedure costs of OSR and EVAR for AAA repair in Korea were USD 1,387 and USD 1,284, respectively. A previous study based on the Korean population reported, however, that the in-hospital cost of EVAR in patients aged <70 years was more than twice that of OSR [ 16 ], suggesting that the similar in-hospital cost in the 2 groups was likely due to the increased cost of treatment of patients aged >70 years. During the study period, AAA-related reinterventions per 100 PY were more than 3-fold higher in the EVAR group, even after adjusting for the reduction in reintervention rate due to the higher early mortality rate of the OSR group and between-group differences in follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…The initial procedure costs of OSR and EVAR for AAA repair in Korea were USD 1,387 and USD 1,284, respectively. A previous study based on the Korean population reported, however, that the in-hospital cost of EVAR in patients aged <70 years was more than twice that of OSR [ 16 ], suggesting that the similar in-hospital cost in the 2 groups was likely due to the increased cost of treatment of patients aged >70 years. During the study period, AAA-related reinterventions per 100 PY were more than 3-fold higher in the EVAR group, even after adjusting for the reduction in reintervention rate due to the higher early mortality rate of the OSR group and between-group differences in follow-up periods.…”
Section: Discussionmentioning
confidence: 99%